2018
DOI: 10.1111/ecot.12155
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between intermediate input imports and export quality in China

Abstract: This paper studies the connection between intermediate input imports and firms’ export quality using firm‐level data from 2000 to 2007. Our regression results show that intermediate input imports promote manufacturing firms’ export quality through ‘variety effects’ and ‘innovation effects’, though the effects are significantly different among firms with different characteristics, and the magnitude of these effects differs across import sources and the quality of imported intermediate inputs themselves. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 69 publications
4
19
0
Order By: Relevance
“…In further estimation results, the signs vary on detailed industries; however, the results remain statistically insignificant (see Appendix A, columns 4-9). The results corroborate with the findings on China (Fan et al, 2015;Xu & Mao, 2018). Moreover, wages in the industries may relate to the skills of the workers.…”
Section: Empirical Results and Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In further estimation results, the signs vary on detailed industries; however, the results remain statistically insignificant (see Appendix A, columns 4-9). The results corroborate with the findings on China (Fan et al, 2015;Xu & Mao, 2018). Moreover, wages in the industries may relate to the skills of the workers.…”
Section: Empirical Results and Discussionsupporting
confidence: 88%
“…More evidence shows that the use imported inputs may induce the firm's production process that allows the firm to generate new exported products (Castellani & Fassio, 2019), expand its range of exported products (Bas & Strauss-Kahn, 2014), and improve its exported product quality (Xu & Mao, 2018). Furthermore, looking at the evidence above, the firm's export performance could be proxied into different variables, but the positive relationship remains dominant in the field of study.…”
Section: The Relationship With Firms' Export Performancementioning
confidence: 99%
“…In this perspective, importing allows firms to identify inputs that match their needs and re-combine resources in order to introduce new/improved products (Andersson and Stone, 2017). This channel of product upgrading has been documented in many recent studies, that have shown that imported inputs can have a strong positive effect on the ability of firm to start selling new products (Goldberg et al 2010;Colantone and Crinò, 2014) and increase the quality and scope of exported products (Feng et al, 2016;Xu and Mao, 2018).…”
Section: The Role Of New Imported Inputsmentioning
confidence: 97%
“…Considering the imperfect substitution between foreign and domestic inputs, imported inputs can realize the optimal configuration of inputs available both at home and abroad. By importing a wide variety of intermediate goods, which can ultimately improve firms' productivity, firms can boost their ability to introduce new and/or higher quality products, which can eventually be exported (Ethier, 1982;Halpern et al, 2015;Xu and Mao, 2018). In this perspective, importing allows firms to identify inputs that match their needs and re-combine resources in order to introduce new/improved products (Andersson and Stone, 2017).…”
Section: The Role Of New Imported Inputsmentioning
confidence: 99%
See 1 more Smart Citation